Development of thermal insulation material using coconut and kenaf fiber for heat recovery enhancement - Shah, R E; Saadon, S; Rahman, N K; Abdellatif, N (Institute of Physics, 2024)
In line with the world’s Sustainable Development Goals (SDG), Malaysia aims to have a clean future energy. The main problem facing the energy revolution is the low conversion efficiency of low-grade heat to useful energy. During the process, a significant fraction of thermal energy is generally lost to the environment as waste heat. Waste heat accounts for 20-50% of industrial energy use, with Southeast Asia processing 40 million tonnes of oil equivalent.Heat losses especially in engines can reduce efficiency, leading to extensive studies to reduce heat loss and improve thermal performance. Heat recovery systems are being studied to recover lower-grade energy, but to the extent of the authors' knowledge, the majority of them are not economically effective for low temperature waste heat. Therefore, the objectives of this study are to develop low thermal conductivity material for thermal insulators based on natural fibre and investigate their impact on thermal performance. The natural fibre-based materials that were chosen in this study are coconut husk and kenaf fibre due to their supposedly low thermal conductivity level and availability in the Southeast Asia region. The specimens were prepared using two different methods; the first two specimens using needle felting method and for the other two specimens epoxy resin was reinforced to bind the material together to become a polymer. The results revealed that coconut husk fibre reinforced with resin has the lowest thermal conductivity value among the four specimens with 0.0410 W/m.K and the lowest overall heat transfer coefficient of 2.73 W/m2.K, making it a possible thermal insulator to be proposed for heat recovery.